Gender Based Conversation Topics of Japanese Native Speakers on Contact Situations with Japanese Learners of Indonesia: First-Time Meeting Encounter - Sonda Sanjaya; Meira Anggia Putri; Arsyl Elensyah Rhema Machawan (Universitas Negeri Semarang, 2023)
This study aims to observe the trends in the categories and types of topics raised by male and female Japanese speakers in conversations with contact situations (with Indonesian speakers) at the first meeting. The conversation is conducted via roleplay in the Japanese language with two settings: a conversation at a cultural exchange event at a university in Indonesia (first setting) and a conversation on a train in Indonesia (second setting). The experiment involved 20 groups consisting of 10 male conversation groups and 10 women's conversation groups. Each group consists of one Japanese-speaking student and one Indonesian-speaking student. Conversations were conducted online using ZOOM and were recorded by researchers. Conversation topics were collected using the conversational engagement-free listening technique and the note-taking technique, in which the researcher listened to the recorded conversations and recorded the topics raised by Japanese speakers. From the data obtained, it is known that male and female Japanese speakers, both in the first and second settings, mainly raise topics related to the Indonesian-Japanese situation and culture. Topics in the category of personal information are also often raised by male and female Japanese speakers in both the first and second settings. In addition, judging from the number of types of topics and the number of occurrences of topics, female Japanese speakers tend to focus less on specific topics. In contrast, male Japanese speakers tend to focus on specific topics.